The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1037/h0076145
|View full text |Cite
|
Sign up to set email alerts
|

A pregroup training technique for encounter group stress.

Abstract: The purpose of this study was to determine the efficacy of induced affect as a pregroup training experience for coping with stress related to participation in an encounter group. Twenty-six subjects who volunteered to participate in an encounter group randomly were assigned to three treatment groups, induced-affect training plus the encounter group, induced-affect training only, and encounter group only. The following hypotheses were supported: (a) Group participants who did not receive the induced-affect preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Curran (1976) found that pretherapy training was an effective method of reducing clients' manifest anxiety prior to initiation of group therapy. In another approach, Zarle and Willis (1975) used a method of induced affect to reduce the level of anxiety and other intense reactions to encounter group participation. The technique of induced affect provided an opportunity to experience intense affective arousal and its subsequent control prior to group.…”
Section: Preparatory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curran (1976) found that pretherapy training was an effective method of reducing clients' manifest anxiety prior to initiation of group therapy. In another approach, Zarle and Willis (1975) used a method of induced affect to reduce the level of anxiety and other intense reactions to encounter group participation. The technique of induced affect provided an opportunity to experience intense affective arousal and its subsequent control prior to group.…”
Section: Preparatory Methodsmentioning
confidence: 99%
“…The three methods that have been used most often to prepare clients for therapy systematically and which have been shown to affect process and outcome variables include: (a) role-induction training in which the client participates in structured didactic sessions prior to beginning therapy (e.g., Yalom et al, 1967); (b) vicarious pretraining based on imitation learning and modeling procedures (e.g., Truax et al, 1968;Whalen, 1969); and (c) programs in which the client is presented with study materials designed to orient him or her to therapy (e.g., Martin and Shewmaker, 1962). Although a major emphasis has been on developing appropriate in-group behavior (roles), different methods also focus in varying degrees on goals, processes, and developing coping mechanisms to deal with anxiety related to group participation (e.g., Zarle and Willis, 1975). …”
Section: Preparatory Methodsmentioning
confidence: 99%
“…Pretraining has been used with populations ranging from students in analog studies to clients participating in encounter or support groups (Muller & Scott, 1984;Zarle & Willis, 1975). Unfortunately, pretraining research has been less focused on populations that are at risk for experiencing interpersonal or task-orientation difficulties.…”
Section: Populations At Risk For Group Skill Deficitsmentioning
confidence: 98%
“…addressed behaviors ranging from positive interpersonal group behavior, such as self-disclosure and cohesion (Palmer, Baker, & McGee, 1997;Santarsiero, Baker, & McGee, 1995) to affective domains, such as anxiety and neuroticism (Sklare, Petrosko, & Howell, 1993;Zarle & Willis, 1975). Despite the general positive endorsement for attending to interpersonal processes in group psychotherapy, research on the benefits of pretraining of interpersonal process skills remains controversial (Piper & Perrault, 1989).…”
mentioning
confidence: 98%
“…Four skills have been the consistent focus in these studies: self-disclosure (D'Augelli and Chinsky, 1974;Evensen and Bednar, 1978;Piper et al, 1979;Wogan et al, 1977), interpersonal feedback (D'Augelli and Chinsky, 1974;DeJulio et al, 1979;Evensen and Bednar, 1978;Wogan et al, 1977), here-and-now interaction (D'Augelli and Chinsky, 1974;DeJulio et al, 1979;Piper et al, 1979), and anxiety management (Zarle and Willis, 1975). As with general information, content designed to teach specific skills has had a significant effect on both group process and group outcome.…”
mentioning
confidence: 97%